PENGARUH COST OF LOANABLE FUND (COLF) DAN TINGKAT SUKU BUNGA SERTIFIKAT BANK INDONESIA (SBI) TERHADAP JUMLAH KREDIT YANG DIBERIKAN - Erisandi Erisandi (Prodi Administrasi Bisnis FISIP Universitas Tulang Bawang Lampung, 2021)
This study aims to analyze the effect of the Cost of Loanable Fund (COLF) and the interest rate of Bank Indonesia Certificates (SBI) on the amount of credit granted. This research was conducted on PT.Bank Mandiri, Tbk 2000 - 2012. The results showed that partially Cost of loanable funds affect the amount of credit significantly while partially the interest rate of Bank Indonesia Certificates has no effect on the amount of credit significantly. Meanwhile, simultaneous test results show the Cost of loanable Fund and SBI have a significant effect on the amount of Loans Provided. The advice given to Bank Mandiri is that the bank management must be able to maintain the appropriate Cost of loanable Fund value. This is because based on the results of empirical research in the field of Cost of loanable funds have a strong and strong correlation to the amount of credit provided, in relation to the SBI which is a factor Given and Bank Indonesia policy, Bank Mandiri must be able to follow and make appropriate policies to improve the credit given at the optimum point. Keywords: Cost of loanable Fund, Bank Indonesia Certificates, Total Credit